2020
DOI: 10.3389/fonc.2020.543817
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of microRNA Biomarkers for Diagnosis, Prognosis, and Therapy in Patients With Clear Cell Renal Cell Carcinoma

Abstract: The ever-increasing morbidity and mortality of clear cell renal cell carcinoma (ccRCC) urgently demands updated biomarkers. MicroRNAs (miRNAs) are involved in diverse biological processes such as cell proliferation, differentiation, apoptosis by regulating their target genes’ expression. In kidney cancers, miRNAs have been reported to be involved in tumorigenesis and to be the diagnostic, prognostic, and therapeutic response biomarkers. Here, we performed a systematic analysis for ccRCC-related miRNAs as bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…In the area of radiomic signature, the radiomic features that were selected as relative factors of prognosis in our study might reflect the degree of tumor progression and assist in the evaluation of postoperative disease progression, treatment effect, and prognosis prediction of KIRC patients. In the area of genomic analysis, identification of specific molecular biological characteristics and regulatory mechanism could not only assist in management and surveillance for KIRC patients but also improve the diagnosis, prognosis, and therapeutic strategy choices for KIRC patients (48)(49)(50)(51). In this study, we are the first to provide a predictive nomogram that integrates radiomic and clinicopathological characteristics for predicting the PFI of KIRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the area of radiomic signature, the radiomic features that were selected as relative factors of prognosis in our study might reflect the degree of tumor progression and assist in the evaluation of postoperative disease progression, treatment effect, and prognosis prediction of KIRC patients. In the area of genomic analysis, identification of specific molecular biological characteristics and regulatory mechanism could not only assist in management and surveillance for KIRC patients but also improve the diagnosis, prognosis, and therapeutic strategy choices for KIRC patients (48)(49)(50)(51). In this study, we are the first to provide a predictive nomogram that integrates radiomic and clinicopathological characteristics for predicting the PFI of KIRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to Sorafenib was increased in association with miR-21 and miR-200 [114,115]. Zheng et al has reported that miR-30a, inhibitors of autophagy, is downregulated in RCC cells and tissues in correlation to the upregulation of its target, Beclin-1.…”
Section: Mirnas In Rcc Therapy and Future Application In Clinical Practicementioning
confidence: 99%
“…214,215 As for most cancers, abnormal expression of miR-221 is also involved in the process of carcinogenesis and disease progression via the regulation of cell proliferation, migration, and invasion in RCC. 216 Szabò et al investigated the miR-21 and miR-221 expression in renal tumor tissues. They reported that that both miRs were overexpressed (and co-expressed in 79.2%) in tissue samples of RCC compared with normal renal tissue (p < 0.001 and p < 0.05 for miR-21 and miR-221, respectively).…”
Section: Renal Cell Carcinoma Renal Cell Carcinoma (Rcc)mentioning
confidence: 99%